Analisis Semiotika Roland Barthes Pada Arsitektur Masjid Raya Sheikh Zayed Solo Sebagai Destinasi Wisata Religi - Anisa Dwi Ipmawati; Hodijah, Ooh (PT. Intelek Cendikiawan Nusantara, 2024)
This research analyzes the architecture of the Sheikh Zayed Grand Mosque in Solo using Roland Barthes' semiotic approach. This mosque is a building that has important symbolic meaning as a tribute to Sheikh Zayed bin Sultan Al Nahyan, the first president of the United Arab Emirates. The research method used is descriptive qualitative with data collection through observation and literature study. The results of semiotic analysis show that architectural elements such as domes, minarets, mosque floors and ornaments in mosques contain meanings and symbols related to Islamic culture and religion. The conclusion of this research is that by using Roland Barthes' semiotic analysis, we can gain a deeper understanding of the meaning and significance of the semiotic elements in the Sheikh Zayed Grand Mosque, Solo. It is hoped that this research can contribute to the development and study of mosque architecture and expand understanding of the application of semiotic theory in the art of architecture.